2018
DOI: 10.3390/nu10081050
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources of Energy and Nutrients of Public Health Concern and Nutrients to Limit with a Focus on Milk and other Dairy Foods in Children 2 to 18 Years of Age: National Health and Nutrition Examination Survey, 2011–2014

Abstract: Many children are not meeting current nutrient recommendations. The objective of this study was to determine the food sources of energy, nutrients of public health concern, and nutrients to limit with a focus on dairy foods. Twenty-four-hour dietary recall data from children 2–5 (n = 1511), 6–11 (n = 2193), and 12–18 years (n = 2172) participating in NHANES 2011–2014 were analyzed. Energy, fiber, calcium, potassium, vitamin D, added sugars, saturated fatty acids (SFA), and sodium intakes were sample-weighted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 58 publications
3
43
1
Order By: Relevance
“…Although the majority of adolescents in our study reported drinking skim milk, rather than homogenized (3.25%) milk, most still consumed ice cream or frozen yoghurt as well. This contrasts with reports from other high-income countries, where dietary intake of dairy products amongst adolescents is low [9,24,25]. At a population level, this is encouraging.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Although the majority of adolescents in our study reported drinking skim milk, rather than homogenized (3.25%) milk, most still consumed ice cream or frozen yoghurt as well. This contrasts with reports from other high-income countries, where dietary intake of dairy products amongst adolescents is low [9,24,25]. At a population level, this is encouraging.…”
Section: Discussioncontrasting
confidence: 91%
“…Adolescence is a critical window for adequate calcium intake, due to intensive bone and muscle development, and the need to optimise peak bone mass [8]. Milk is the top food source of calcium for children aged 2-18 years [9]. In a typical western diet, cow's milk is a common source of calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a cross-sectional study on a sample of GENESIS cohort of 2287 children (aged one to 5 years) concluded that about 80% of the children had a poor diet associated with low fruit, vegetable and grains intake and high saturated fat intake [61]. Moreover, in the NHANES study, for children 2-5 and 6-11 years old, the fruit and vegetables were the 7º and 16º ranked food sources of energy, respectively [32].…”
Section: Contribution Of Food Groups To Energy Intakementioning
confidence: 99%
“…Furthermore, it is important to emphasize that the consumption of milk and dairy products promote adherence to the nutrient recommendations and may protect against the most prevalent non-communicable chronic diseases [8,9]. Similarly, in the NHANES study, found that milk was the top food source of energy in all ages [32].…”
Section: Contribution Of Food Groups To Energy Intakementioning
confidence: 99%
See 1 more Smart Citation